2019
DOI: 10.3390/app9214501
|View full text |Cite
|
Sign up to set email alerts
|

Application and Evaluation of Energy Conservation Technologies in Wastewater Treatment Plants

Abstract: High energy consumption is an important issue affecting the operation and development of wastewater treatment plants (WWTPs). This paper seeks energy-saving opportunities from three aspects: energy application, process optimization, and performance evaluation. Moreover, effective energy-saving can be achieved from the perspective of energy supply and recovery by using green energy technologies, including wastewater and sludge energy recovery technologies. System optimization and control is used to reduce unnec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 176 publications
(202 reference statements)
1
4
0
1
Order By: Relevance
“…Although the EEO for industrial processes can differ by one or two orders of magnitude and depends on the process parameters as well as the scale of the apparatus, our results are comparable to the ones reported in the literature and related to the refence AOP. The minimum value of 7 kWh/m 3 observed at 400 kPa is below the EEO of ultrasonic cavitation, as commonly demonstrated in the scientific literature [8,10,12,[67][68][69][70][71] and is in the range of Ozonation, O3/H2O2, UV/persulfate, O3/UV UV/H2O2 [67][68][69][70][71][72][73]. Moreover, these values have been obtained for pure hydrodynamic cavitation and can be consistently decreased by the application of hybrid techniques including cavitation and H2O2 or O3.…”
Section: Energy Efficiencysupporting
confidence: 63%
“…Although the EEO for industrial processes can differ by one or two orders of magnitude and depends on the process parameters as well as the scale of the apparatus, our results are comparable to the ones reported in the literature and related to the refence AOP. The minimum value of 7 kWh/m 3 observed at 400 kPa is below the EEO of ultrasonic cavitation, as commonly demonstrated in the scientific literature [8,10,12,[67][68][69][70][71] and is in the range of Ozonation, O3/H2O2, UV/persulfate, O3/UV UV/H2O2 [67][68][69][70][71][72][73]. Moreover, these values have been obtained for pure hydrodynamic cavitation and can be consistently decreased by the application of hybrid techniques including cavitation and H2O2 or O3.…”
Section: Energy Efficiencysupporting
confidence: 63%
“…Compared to other countries, it constitutes a relatively low value. The consumption of electricity by all WWTPs in Europe was calculated as 27 TWh/year [67]. A constant development of the municipal infrastructure indicates an increase in the energy consumption for WWTP in Poland, even up to 5.5 TWh/year, which will comprise ca.…”
Section: Biogas Utilization At Wwtps In Polandmentioning
confidence: 99%
“…In a similar context, Sun et al, [12] reported on the application and evaluation of energy conversion technologies in wastewater treatment plants. The reason is that high energy consumption is a critical issue influencing the operation and sustainability of wastewater treatment plants (WWTPs).…”
Section: Resultsmentioning
confidence: 99%
“…(a) First, there are those that investigate the application of membrane treatment processes, either directly [1] (b) second, there are studies that investigate the application of adsorptive processes for the removal of contaminants from waters, such as arsenic, lead, nickel or chromate [2][3][4][5][6], but also assessed the health effects of their exposure to humans [7]. (c) third, there are studies that include novel aspects of oxidative treatment [8,9] and (d) fourth, studies that examine wastewater treatment efficiency, testing new type reactors [10], minimizing the sewage sludge [11] or energy minimization and conversion and in wastewater treatment facilities [12,13].…”
Section: Introductionmentioning
confidence: 99%